SODIUM POTASSIUM ROOT DEFECTIVE1 regulates FLOWERING LOCUS T expression via the microRNA156–SQUAMOSA PROMOTER BINDING PROTEIN-LIKE3 module in response to potassium conditions. (14th December 2017) - Negishi, Katsuya; Endo, Motomu; Abe, Mitsutomo; Araki, Takashi
Abstract: To determine flowering time, plants perceive multiple environmental stimuli and integrate these signals in the regulation of a florigen gene, FLOWERING LOCUS T ( FT ). It has been known that nutrient availability affects flowering time in both laboratories and fields. Nitrogen (N), phosphorus (P) and potassium (K) are the three major macronutrients which are important for plant growth and development. Although N and P stimuli can alter the expression of regulators of FT including microRNA156 (miR156) and miR156-targeted transcription factors of the SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) family, how K + conditions affect flowering is still unclear. We focused on SODIUM POTASSUIM ROOT DEFECTIVE1 ( NaKR1 ) whose mutant plants showed Na + and K + overaccumulation and late flowering. It was reported that NaKR1 is involved in the phloem transport of FT protein. Here we report that NaKR1 is also required for the promotion of FT expression in long-day conditions. NaKR1 affects the accumulation of miR156 and SPL3 expression, suggesting that NaKR1 regulates FT expression in part through the miR156–SPL3 module. The late-flowering phenotype of the nakr1-1 mutant was partially suppressed under low K + conditions, and miR156 abundance and SPL3 expression in the nakr1-1 mutant and, to a lesser extent, in wild-type plants responded to K + conditions. Taken together, our findings suggest that the miR156–SPL3 module mediates regulation of FT expression by NaKR1 in response to K + conditions. Finally, we propose a model in which NaKR1 plays dual roles in regulation of flowering, one in the regulation of florigen production, the other in that of florigen transport.